MATHEMATICAL RESILIENCE: VALIDITY AND RELIABILITY WITH RASCH MODEL AND SPSS IN SENIOR HIGH SCHOOL - Ayu Faradillah; Citra Septiana (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
Validity and reliability testing is very important for an instrument, both of which can determine whether the instrument used is good or not. This study intends to break down the correlation of the the mathematical resilience questionnaire for for studies utilizing SPSS and the Rasch Model. The research method used is a quantitative survey method, with a total of 207 students in one of the senior high schools in Jakarta. This study uses a mathematical resilience questionnaire which was adopted from other studies in which there are 4 indicators in the questionnaire. Testing the validity of the mathematical resilience questionnaire using the Rasch Model with the WinSteps 3.73 application showed that there were three invalid items (I9, I16, I18), and six items (I7, I11, I12, I13, I17, I19) which only met 1 condition. , so 26 must be retained because the item is satisfied. While the validity test on SPSS 24.0 which is seen from the Pearson correlation value, the results show that 6 items are invalid, namely (I7, I8, I9, I11, I16, I18), so the rest of the other items must be maintained because they meet the criteria. Meanwhile, the reliability calculation is (α = 0.84). The use of two different applications, namely Winsteps and SPSS, stated that the mathematical resilience questionnaire was declared valid and reliable. This is obtained by eliminating 8 statement items in the questionnaire.